1989
DOI: 10.1136/emj.6.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Scaphoid tubercle tenderness: a better indicator of scaphoid fractures?

Abstract: SUMMARYTenderness in the anatomical snuff box (ASB) has long been accepted as an indicator of a possible scaphoid fracture. The longitudinal axis of the scaphoid lies in an anteroposterior plane, perpendicular to the remainder of the carpal bones, in the radially deviated wrist. The scaphoid tubercle can therefore be easily and accurately palpated on the palmar aspect of the radially deviated wrist.This study was devised to determine if tenderness over the scaphoid tubercle (ST) was superior to ASB tenderness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 4 publications
1
27
0
4
Order By: Relevance
“…For example, whereas Grover 12 found the SCT to be 100% sensitive and 80% specific, Esberger 14 showed that it only had sensitivity of 71% and specificity of 22%. On the other hand, Freeland 15 found that the STT had a sensitivity of 87% and specificity of 57%, which notably, is more specific than the widely accepted ASB tenderness test. Pain over ASB on pronation followed by ulnar deviation of the affected wrist also gave a specificity of only 52%.…”
Section: Diagnostic Examinationmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, whereas Grover 12 found the SCT to be 100% sensitive and 80% specific, Esberger 14 showed that it only had sensitivity of 71% and specificity of 22%. On the other hand, Freeland 15 found that the STT had a sensitivity of 87% and specificity of 57%, which notably, is more specific than the widely accepted ASB tenderness test. Pain over ASB on pronation followed by ulnar deviation of the affected wrist also gave a specificity of only 52%.…”
Section: Diagnostic Examinationmentioning
confidence: 95%
“…17,20,29 However, continued immobilisation without a definitive diagnosis may extend over several weeks, during which the patient is unable to live and work normally. Recent studies have shown that the incidence of proven scaphoid fractures from clinically suspected scaphoid fractures is only 2-12% 2,3,15,19 and, therefore, the need to treat all patients in full scaphoid cast is questionable. DaCruz et al 19 demonstrated that by resting all suspected scaphoid injuries in a broad arm sling initially and reassessing them within a week, the number of patients that required cast immobilisation was significantly reduced.…”
Section: Early Treatment and Duration Of Immobilisationmentioning
confidence: 99%
“…Fifteen studies published between 1982 and 2009 assessed the diagnostic accuracy for various physical examination tests, either in isolation or in combinations, including signs such as swelling or discoloration, as well as symptoms like anatomical snuffbox tenderness, scaphoid tubercle tenderness, clamp sign, resisted pronation or supination, thumb compression-induced pain, and US pain. 5,14,[17][18][19][21][22][23]39,[41][42][43][44][45][46] None were from the United States, and 12 were from Europe. These were all prospective case series, and 11 were ED-based, while two were orthopedic clinic studies and two did not report their clinical settings.…”
Section: History and Physical Examinationmentioning
confidence: 99%
“…Alternatively, pain with digital pressure over the scaphoid tubercle may indicate scaphoid fracture. 14 The scaphoid tubercle is the palpable prominence at the level of the distal flexor crease of the extended and radial-deviated wrist (Data Supplement S2, available as supporting information in the online version of this paper). The Watson test, also called "the scaphoid shift," actually evaluates scapholunate pathology, but has been reported as a test for scaphoid fracture.…”
mentioning
confidence: 99%
“…The patient also had point tenderness to palpation in the anatomical snuff box of the left wrist. 1 Due to concern for hip and wrist fractures, which are often radiographically occult initially after injury, the physical therapist ordered radiographs of the left …”
mentioning
confidence: 99%